(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The syudy aims to analyses the impact of the foreign exchange window on the exchange rate of the iraqi dinar for the period 2003-2021. rentier economies that suffer from inefficient traditional channels for the transfer of monetary policy to the real sector due to their disrupted economic structure and heavy dependence on imports to meet domestic demand apply direct instruments such as the foreign exchange window. the exchange rate is a critical tool used by the monetary authority to maintain price stability and target inflation. the foreign exchange sale window is an effective mean of directly affecting the exchange rate and is an interim tool for crossing a transitional period and ensuring monetary stability during this period. the research concluded that the foreign exchange window affects the exchange rate of the iraqi dinar and this effect was uneven during the study period. the results of the study showed that the exchange rate of the iraqi dinar responded to the monetary authoritys porcedures of employing part of the reserves to maintain its stability during the period 2003-2010 while the period 2011-2020 showed a weak response to the central bank interventions and thus higher gap between the nominal and parallel exchange rate.